Acute effects of psychological relaxation techniques between two physical tasks. Issue 3 (1st February 2017) - Pelka, M.; Kölling, S.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M.
ABSTRACT: The concept of recovery strategies includes various ways to achieve a state of well-being, prevent underrecovery syndromes from occurring and re-establish pre-performance states. A systematic application of individualised relaxation techniques is one of those. Following a counterbalanced cross-over design, 27 sport science students (age 25.22 ± 1.08 years; sports participation 8.08 ± 3.92 h/week) were randomly assigned to series of progressive muscle relaxation, systematic breathing, power nap, yoga, and a control condition. Once a week, over the course of five weeks, their repeated sprint ability was tested. Tests (6 sprints of 4 s each with 20 s breaks between them) were executed on a non-motorised treadmill twice during that day intermitted by 25 min breaks. RM-ANOVA revealed significant interaction effects between the relaxation conditions and the two sprint sessions with regard to average maximum speed over all six sprints, F (4, 96) = 4.06, P  = 0.004, = 0.15. Post-hoc tests indicated that after systematic breathing interventions, F (1, 24) = 5.02, P  = 0.033, = 0.18, participants performed significantly better compared to control sessions. As the focus of this study lied on basic mechanisms of relaxation techniques in sports, this randomised controlled trial provides us with distinct knowledge on their effects, i.e., systematic breathing led to better performances, and therefore, seems to be a suited relaxation method during high-intensity training.